Strategi Pemasaran Digital Melalui Media Sosial Dan Inovasi Kemasan Bagi Umkm “Pawon Cilik Mama Wendeeeh” Di RT. 56 Kelurahan Gunung Sari Ilir, Balikpapan - Sinaga, Ovigeria Subroto; Adelia Rahmawati; Abid Adnan At Thohiry (Komunal Jurnal Pengabdian Masyarakat, 2024)
Field Work Practice (PKL) or also known as Innovation Development (PI) is a service activity of STIE Madani Balikpapan students to the community, especially to Micro, Small and Medium Enterprises (MSMEs). The target of MSMEs targeted in the Innovation Development Program (PI) in this group is Pawon Cilik Mama Wendeeeh which is located in RT 26 Gunung Sari Ilir Village, Central Balikpapan District. The objectives of the Innovation Development activities are: 1) Assisting in the assistance of making Google Maps; 2) Assisting in making product packaging sticker designs; 3) Assisting in making digital payment tools using QR Code scans and can be scanned, namely QRIS; and 4) Assisting in making “Pawon Cilik Mama Wendeeeh” UMKM business banners. The result of Innovation Development in group 1 Gunung Sari Ilir Village is to form this MSME to be more developed in terms of more advanced product visuals, as well as digital modernization in terms of payment tools which initially only used cash or cash transactions to non-cash payments or using QRIS scans.